Histomorphological evaluation of colon lesions - Shah, Nirali; Jaisar, Naimesh; Patel, Naman; Shah, C. K. (International Journal of Research in Medical Sciences, 2017)
Background: Both macroscopic and microscopic appearance helps in identification of the colon lesion which supports in the treatment of the patient in a better way. The authors were aimed at the prevalence of various colon lesions site wise distribution of various neoplastic and non-neoplastic lesions of the patients and to compare the distribution according to their age, sex and site. Methods: A retrospective study was designed to study of various intestinal biopsies sent for histopathological examination at Department of Pathology, N.H.L. Municipal Medical College and V.S. Hospital, Ahmedabad, from January 2015 to December 2016 for period of 2 years. The study was based on the histomorphological evaluation of colon lesions received during the study period. Results: A male preponderance was seen in the incidence of tumors irrespective of tumor type and site of tumor and M:F ratio was 1.64:1. In the large intestine, adenocarcinomas were the commonest malignant tumor. 46 cases (62.61%) were reported. The highest occurrence of appendicitis is in the 2nd and 3rd decade. Conclusions: The study revealed that various types of lesions in large intestine along with the age group and gender affected more. Male patients were majorly affected. Morphological identification helped to diagnose the type of lesion for early diagnosis. This study focuses the role of histopathological identification in early diagnosis of the disease so that the survival rates in such cases will be increased.